Widmo merytokracji kadrowej = The spectre of personnel meritocracy - Kwiatkowski, Mariusz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
After 1989, as sociologists, political scientists, columnists and other observers unanimously claim, it has not been possible to implement and consistently apply meritocratic rules of filling public posts. A major role is still played by such criteria as political affiliation or candidates` personal relations.
Keywords: sektor publiczny; dobór kadr; kadra kierownicza